1980
DOI: 10.1007/bf00256997
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative deep-vein thrombosis by low-dose heparin in open prostatectomy

Abstract: A double-blind trial was designed to investigate the efficacy of low-dose heparin in preventing deep-vein thrombosis (DVT) after open prostatectomy... The diagnosis of DVT was established by the 125I-fibrinogen test. The incidence of DVT was 39.4% in the control group (33 patients) and 9.7% in the heparin group (31 patients) (p less than 0.01). These results suggest that low-dose heparin effectively prevents DVT after open prostatectomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The incidence of symptomatic DVT after major urologic surgery has decreased from 15-40% as reported up to 30 years ago [4,5] to more contemporary rates of 1-5% [6][7][8] with the introduction of pharmacological prophylaxis, early mobilization and the use of sequential mechanical compression devices. With respect to laparoscopic or robotic-assisted laparoscopic radical prostatectomy (RALP), Secin et al [9] reported a 0.5% incidence of venous thromboemobolism (VTE) in a large retrospective review of 5951 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of symptomatic DVT after major urologic surgery has decreased from 15-40% as reported up to 30 years ago [4,5] to more contemporary rates of 1-5% [6][7][8] with the introduction of pharmacological prophylaxis, early mobilization and the use of sequential mechanical compression devices. With respect to laparoscopic or robotic-assisted laparoscopic radical prostatectomy (RALP), Secin et al [9] reported a 0.5% incidence of venous thromboemobolism (VTE) in a large retrospective review of 5951 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Before routine use of heparin prophylaxis in these patients, the incidence of venous thromboembolism (VTE) in patients undergoing major surgery, including major urological surgery, ranged from 15 to 40% [8,9], but even with adequate prophylaxis and early mobilization VTE rates of 1-5% can still be found [7,10,11]. Furthermore, pulmonary embolism is believed to be a major cause of postoperative mortality [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,6,7,[9][10][11] The overall incidence of DVT was reduced from 39% to 16% (RR 0.41; 95% CI 0.24-0.71). 3,4,[6][7][8]10,11,22 A study of 579 patients having radical prostatectomy did not find any difference in the number of pelvic lymphoceles or blood loss between those receiving LDUH and those not having prophylaxis. 23 The RCTs to study the efficacy of LMWH for VTE prevention in patients undergoing urologic surgery have not been performed.…”
Section: Prophylactic Methods and Recommendationsmentioning
confidence: 99%